Analysing the effect of principal stress rotation on railway track settlement by discrete element method. Issue 9 (27th September 2019) - Bian, Xuecheng; Li, Wei; Qian, Yu; Tutumluer, Erol
Abstract : Principal stress rotation induced by moving loads from trains significantly influences railway track settlement accumulation. The stationary cyclic loading commonly adopted to study railway ballast behaviour under repeated train loading cannot fully represent the effects of principal stress rotation, which needs to be properly considered in both laboratory tests and numerical simulations for a better understanding of ballast deformation behaviour. This paper focuses on studying railway ballast deformation behaviour with an emphasis on particle scale interactions under two different loading scenarios – namely, stationary cyclic and moving wheel loading. A ballasted track model consisting of five sleepers was established based on the discrete-element method (DEM) with realistic polyhedron-shaped elements. The numerical model was validated first based on the testing results from a full-scale high-speed railway testing facility at Zhejiang University. Numerical results clearly indicated that moving wheel loading induced larger principal stress rotation than stationed cyclic loading did. Larger principal stress rotation mobilised higher particle rotation and displacement, which further increased particle rearrangements through individual particle rolling and sliding, and potentially could cause accelerated ballast degradation. It is recommended to consider principal stress rotation in ballast settlement predictions to prevent possible underestimation by stationary cyclic loading and its limitations.